Natural history of chronic hepatitis B virus infection from infancy to adult life -the mechanism of inflammation triggering and long-term impacts - Wu, Jia-Feng; Chang, Mei-Hwei (Journal of biomedical science, 2015)
Chronic hepatitis B virus (HBV) infection in endemic areas usually starts since infancy and early childhood and persists lifelong. The clinical course varies among different chronic infected subjects. Majority of chronic HBV infected children present with immune-tolerant status initially, experience the immune clearance phase with various degree of liver injury during or beyond puberty, and then enter the inactive phase after hepatitis B e antigen (HBeAg) seroconversion. Part of them may have HBV DNA titers elevation with hepatitis flare after HBeAg seroconversion, the so call HBeAg-negative hepatitis flare. Liver cirrhosis, and even hepatocellular carcinoma may develop afterward.The complex course of chronic HBV infection is associated with the age/route of viral acquisition, host factors such as immune and endocrine factors, viral factors, and host-viral interactions. The adrenarche and puberty onset modulate the start of immune clearance and the severity of liver inflammation in chronic HBV infected children. The genotype and phenotype of human cytokines, innate immunity, and human leukocyte antigens are also associated with the onset of immune clearance of HBV and severity of inflammation. Immune escape HBV mutant strains, emerged during the immune clearance phase under host immune surveillance, may cause different impacts on viral biosynthesis, host immune responses, and clinical course.Early events in childhood during chronic HBV infection may serve as important predictors for the later outcome in adulthood. Understanding the mechanisms triggering liver inflammation and their long-term impacts may enhance the development of better and earlier therapeutic strategies for patients with chronic HBV infection.